Derelicts: An Account of Ships Lost at Sea in General Commercial Traffic : And a Brief History of Blockade Runners Stranded Along the North Carolina Coast, 1861-1865 - Sprunt, James, 1846-1924 (Salt Lake City, UT : Project Gutenberg, 2017)
"Derelicts: An Account of Ships Lost at Sea in General Commercial Traffic" by James Sprunt is a historical account written in the early 20th century. The work discusses the fate of numerous vessels that were abandoned at sea, particularly during the American Civil War, detailing blockade runners and other ships lost along the North Carolina coast. It captures the narrative of their journeys, the challenges they faced, and the broader implications of maritime navigation during a turbulent period in U.S. history. The opening of the book sets the stage by introducing the author's long-standing interest in the stories of derelict ships and the blockade runners that encountered various fates during the Civil War. Sprunt reflects on episodes from his own life, including his role as a paymaster on some of these ships, conveying a deep sense of nostalgia and urgency to document these stories before they fade from memory. He establishes that many of these derelict ships still hold their secrets, and introduces the term "derelict" within a legal context, while describing the dangers they pose to maritime traffic. The beginning of the book combines personal recollections, historical insights, and vivid imagery of life at sea, drawing readers into the perilous world of nautical adventures amidst the backdrop of war. (This is an automatically generated summary.)
Release date is 2017-12-31
E-text prepared by deaurider, Graeme Mackreth, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Derelicts; Blockade; North Carolina -- History -- Civil War, 1861-1865